Amplitude of low-frequency fluctuation (ALFF) and fractional ALFF in migraine patients: a resting-state functional MRI study. Issue 6 (June 2016) - Wang, J.-j.; Chen, X.; Sah, S.K.; Zeng, C.; Li, Y.-m.; Li, N.; Liu, M.-q.; Du, S.-l.
Abstract : Aim: To evaluate the amplitude of low-frequency oscillations (LFOs) of the brain in migraine patients using amplitude of low-frequency fluctuation (ALFF) and fractional ALFF in the interictal period, in comparison to healthy controls (HCs). Materials and methods: A total of 54 subjects, including 30 migraineurs and 24 gender- and age-matched HCs completed the fMRI. All the data and ALFF, fALFF analyses were preprocessed with the Data Processing Assistant for Resting-State fMRI (DPARSF). All of the statistical analyses were performed using the REST software to explore the differences in ALFF and fALFF between migraine patients and HCs. Results: In contrast to HCs, migraine patients showed significant ALFF increase in the left medulla and pons, the bilateral cerebellum posterior lobe and right insula. The regions showing decreased ALFF in migraine patients included the bilateral cerebellum posterior lobe, left cerebellum anterior lobe, bilateral orbital cortex, right middle frontal gyrus, bilateral occipital lobe, right fusiform gyrus, and bilateral postcentral gyrus. The fALFFs in migraine patients were significantly increased in the bilateral insular and left orbital cortex, but were decreased in the left occipital lobe and bilateral cerebellum posterior lobe. Conclusion: These ALFF and fALFF alterations in the brain regions of migraineurs are in keeping with the domains associated with pain and cognition. Such brain functional alteration may contribute to further understanding of migraine-related network imbalances demonstrated in previous studies. Highlights: Migraine is a common, paroxysmal, highly disabling primary headache disorder. Resting-state fMRI offers a novel approach to measure spontaneous brain activity in migraine patients The ALFF and fALFF alterations in migraineurs' brain regions are in keeping with the domains associated with pain and cognition.